Antioxidant Effect of Νω-Nitro-L-arginine Methyl Ester (L-NAME) on Global Cerebral Ischemia in a Rat Model - Seif-El-Nasr, Mona; Fahim, Atef T. (Arzneimittelforschung, 2001)
The antioxidant effect of the non-specific nitric oxide synthase inhibitor, Νω- nitro-L-arginine methyl ester (CAS 50903-99-6, L-NAME), was studied in a rat model of global cerebral ischemia. In addition, the influence of low doses of L-NAME on nitric oxide production, measured as nitrate/nitrite end products, was investigated in the ischemic rats. Ischemia was induced by bilateral clamping of the common carotid arteries for 60 min followed by a reperfusion period for 60 min. L-NAME was administered intraperitoneally in the doses of 1 and 3 mg kg−1, twice, immediately after ischemia and 15 min before termination of the experiment The drug decreased the elevated activity of lactate dehydrogenase (LDH, 1.1.1.27) as well as the increased level of lipid peroxide in the rat brain. L-NAME was also capable to normalize the reduced activity of superoxide dismutase (SOD, 1.15.1.1) that was observed after ischemia. Improvement of these parameters in L-NAME-treated rats was parallel to normalization of nitric oxide production in the treated animals. These results indicate that inhibition of nitric oxide synthase, induced by L-NAME, could improve the oxidative status of the rat brain after ischemia.
Keywords: CAS 50903-99-6; Cerebral ischemia, rat; Lactate dehydrogenase; Nω-Nitro-L-arginine methyl ester, antioxidant effect; Superoxide dismutase